Student Teachers’ Vocational Identity Formation: How the Impact of Moral and Ego Development? - Akhmad, Sudaryat Nurdin; Suherman, Uma; Ilfiandra, Ilfiandra; Nadhirah, Nadia Aulia (Journal of Educational Science and Technology (EST), 2024)
The lack of concern teacher education for the formation of vocational identity and the controversy about relation between moral and ego development to identity formation become the reason why this research was conducted. The objective of this research to describe the causal relationship between three constructs. The design used is a cross-sectional survey with descriptive methods. The participants in this study were 465 prospective teacher students at a state university that provides teacher education in Indonesia, who were recruited using a multistage cluster sampling technique. The Defining Issues Test, Ego Development Inventory, and Vocational Exploration and Commitment Questionnaire were used to reveal the data, which were then processed statistically. The configuration of morals and ego in identity formation is mapped in the contingency table. In contrast, the causal analysis is tested through path analysis. From the results of this study, no systematic map was found regarding the configuration of morals and ego in the formation of vocational identity status. Unlike moral considerations, ego development has a positive effect on the vocational identity status of students. Moral development is not correlated with ego development and vocational identity status. This study also successfully revealed theoretical, methodological, and practical implications.